Non-aqueous Isorefractive Pickering Emulsions - Thompson, Kate L. (Langmuir, 2015)
[Image: see text] Non-aqueous Pickering emulsions of 16–240 μm diameter have been prepared using diblock copolymer worms with ethylene glycol as the droplet phase and an n-alkane as the continuous phase. Initial studies using n-dodecane resulted in stable emulsions that were significantly less turbid than conventional water-in-oil emulsions. This is attributed to the rather similar refractive indices of the latter two phases. By utilizing n-tetradecane as an alternative oil that almost precisely matches the refractive index of ethylene glycol, almost isorefractive ethylene glycol-in-n-tetradecane Pickering emulsions can be prepared. The droplet diameter and transparency of such emulsions can be systematically varied by adjusting the worm copolymer concentration.